SPHERICAL ENCOUNTERS OF HUMAN RIGHTS (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
The apotheosis of the globe, global and globalized seems to grow ungainly with authoritative grandeur at our every breath.With continuous adjustments forced upon this model, under constant tension favored by industrialization, consumerism, political conflicts and anthropocene, the most basic human rights are abused and ignored time and time again, all over the world. Is there an alternative to the global view of the world? The paper aims to demonstrate that opposed to the globe as object, symbol and iconography that mediates globalization, and places our view outside earth, the diverse typologies of immersive media such as virtual reality and 360° video projects, fulldome films designed for dome theatres, followed by online interactive 360° webdocumentaries or virtual tours, function as cultural interfaces for the spherical worldview. The research sets out to consider this spherical representation of human rights which re-position its ‘inhabitants’ to perceive the world from within (Ingold) and integrates the multiplicity and diversity of our contemporary societies and cultural representations, sustaining the human rights of the indigenous, marginal and minority. This will be done specifically in relation to Astra Film Festival’s new media program entitled The Future is Now implemented and curated by Adela M. in 2016 and 2017 in Sibiu city, Romania, through case studies that use the virtual reality and 360° video technology. While the sphere, spherical, spheropoiese is presented as the counterdiscourse of the globe, global and globalized, the paper introduces their detailed historical evolution, building a tension that unfolds through the mythologem of the orb and its unconventional dialectical interplay between engagement as a sphere and detachment as a globe, viewpoints that mutually function as paradoxical concurrent perspectives.